Every Woman is Beautiful in Her Own Way: A Qualitative Study on Broad Conceptualization of Beauty in Thai Female Undergraduates - Jinchang, Kamonkan; Jarunratanakul, Prapimpa (Journal of Behavioral Science for Development, 2023)
The present study aimed to study the concept of broadly conceptualizing beauty perceived by female adolescents who had positive body image and to synthesize the broad conceptualization of beauty themes in Thai context. The qualitative study was conducted using in-depth interview technique with female undergraduates. Seventeen key informants who was classified as high positive body image were recruited for semi-structured interview. Data were analyzed through reflexive thematic analysis. ‘Broad conceptualization of beauty’ perceived by Thai adolescents were categorized by 3 themes and 12 sub-themes including 1) external beauty: broad view of physical beauty, body-care, personal dressing styles 2) intrapersonal characteristics: self-confidence, self-acceptance, inner soul and spirituality, intelligence and 3) desirable interpersonal characteristics: nice gestures, positive communal traits, positive attitude towards others, optimism, and positive emotions. The results can be beneficial guideline to involved health professions as well as relevant organizations for treating body image problems and enhancing healthy body image by broadening the conceptualization of beauty. These findings also suggest the conceptual framework of broad conceptualization of beauty contributing to scale development and future studies in Thai women.